ADAM10 gene expression in the blood cells of Alzheimer's disease patients and mild cognitive impairment subjects. (May 2015) - Manzine, Patricia Regina; Marcello, Elena; Borroni, Barbara; Kamphuis, Willem; Hol, Elly; Padovani, Alessandro; Nascimento, Carla Crispim; de Godoy Bueno, Patricia; Assis Carvalho Vale, Francisco; Iost Pavarini, Sofia Cristina; Di Luca, Monica; Cominetti, Márcia Regina
Abstract ADAM10 is a potential biomarker for Alzheimer's disease (AD). ADAM10 protein levels are reduced in platelets of AD patients. The aim was to verify the total blood and platelet ADAM10 gene expression in AD patients and to compare with mild cognitive impairment (MCI) and healthy subjects. No significant differences in ADAM10 gene expression were observed. Therefore, the decrease of ADAM10 protein in platelets of AD patients is not caused by a reduction in ADAM10 mRNA. Further studies must be performed to investigate other pathways in the down regulation of ADAM10 protein.